2000
DOI: 10.2169/internalmedicine.39.537
|View full text |Cite
|
Sign up to set email alerts
|

Allele Frequency of Human Endothelial Nitric Oxide Synthase Gene Polymorphism in Abdominal Aortic Aneurysm.

Abstract: Objective This study was performed to examine the role of the endothelial constitutive NOsynthase (ecNOS) gene in patients with abdominal aortic aneurysm (AAA). Methods We determined the distributions of polymorphism in intron 4 of the ecNOS (ecNOS4) gene, amplified by polymerase chain reaction, and comparedthe allele frequencies between subjects with abdominalaortic aneurysms (AAAs) and healthy individuals.Patients Fifty-eight patients with AAAsand 410 racematched healthy controls were studied. Results Two al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 12 publications
3
21
0
2
Order By: Relevance
“…21,22 There are only 2 reports, which focus on the link between functional polymorphisms of eNOS gene and AAA. Kotani et al 25 reported that 4a/4b polymorphism of eNOS gene is not associated with presence of AAA. However, they also found strong association between 4a/4b polymorphism of eNOS gene and elective repair of AAA, reflecting the expansion of AAA.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 There are only 2 reports, which focus on the link between functional polymorphisms of eNOS gene and AAA. Kotani et al 25 reported that 4a/4b polymorphism of eNOS gene is not associated with presence of AAA. However, they also found strong association between 4a/4b polymorphism of eNOS gene and elective repair of AAA, reflecting the expansion of AAA.…”
Section: Resultsmentioning
confidence: 99%
“…Since the role of nitric oxide in cerebral vasospasm (after SAH) was discovered, this turned into a subject of study for neuroscientists [9,21,33,37]. Therefore, genes encoding NO isoforms may exhibit aberrations that could account for individual differences in vasomotor responses following aneurysmal rupture.…”
Section: Genetic Enos Polymorphism X Pós-sah Cerebral Vasospasmmentioning
confidence: 99%
“…The last polymorphism is a variable number tandem repeat (VNTR) located in intron-4 of the gene and consists of either four or five 27-base pair (bp) repetitions. This one is associated with AMI [37] and aortic aneurysm [21].…”
Section: Introductionmentioning
confidence: 98%
“…One polymorphism consists of a 27 base pair repeat, present in intron 4 of the eNOS gene. Commonly, 5 repeats are identified at this polymorphic site, however, when analysing patients with AAA, it was found that 4 repeats at this site may be associated with rapid progression of AAA (Kotani et al, 2000). A further polymorphism is the G894T, in which the rarer T allele has been found to be more frequent in AAA patients compared with age/sex-matched controls (Fatini et al, 2005b).…”
Section: Nitric Oxide Synthase Genementioning
confidence: 99%